Keterampilan Bertanya Saintifik Anak Usia 5-6 Tahun - Edi Hendri Mulyana; Qonita Qonita; Elan Elan; Risbon Sianturi; Serfa Az-Zahra Sakinah; Indri Anggraeni (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2024)
The critical thinking ability of early childhood is the basis of skills that can be developed through various learning so that scientific questioning skills are formed in understanding each learning context. This type of research uses a qualitative approach. Data collection techniques in this research are through observation, interviews, and documentation data collection. The subjects of this research were 20 children in group B. The results of this research showed that the questioning skills of children in group B of the National Plus Joy Kids Kindergarten were very active, demonstrated by the class's activeness during learning using the audio-visual method, namely showing an interactive learning video so that it could generate Children's curiosity is well stimulated.